Perceived Social Support and Self-Care Behaviors among Hypertensive Patients in Bangladesh - Ara, Mst. Husne; Anowar, Mohammad Nurul; Islam, Md. Shariful; Shom, Ela Rani; Habib, Ahasan (International Journal of Research in Medical Surgical Nursing, 2024)
Background: Hypertension is a common chronic condition that develops as blood arteries narrow, causing the heart to exert excessive pressure against vessel walls and forcing the heart to work harder to maintain blood circulation. Hypertension is the most common cause of cardiovascular disease and early death worldwide. Managing hypertension involves not just decreasing blood pressure with anti-hypertensive drugs but also minimizing its repercussions through self-care activities. Perceived social support influences positive psychological outcomes such as resilience, self-efficacy, and self-esteem. Objective: The study assessed hypertensive patients’ perceived social support and self-care behaviors. Methods: A cross-sectional descriptive study was conducted at the tertiary level hospital in Bangladesh. The study populations were patients aged 18 years or older who had been diagnosed with hypertension for at least 1 year, were taking anti-hypertensive medication, and Willingness to participate in the study. The data were collected from February to March 2023. The sample size was 112. A convenience sampling technique was used to select the sample size. Data was collected with a structured questionnaire through face-to-face interviews. Data were analyzed using both descriptive and inferential statistics using SPSS version 22. The study’s findings will contribute to developing training and education programs on perceived social support and self-care behaviours among hypertensive patients in Bangladesh. Results: The current study found that hypertensive patients’ average perceived social support was relatively high and moderate self-care behaviors. Conclusion: In summary, self-care recognizes individuals as active agents in managing their health care in areas including health promotion, disease prevention and control, self-medication, providing care to dependent persons, and rehabilitation, including palliative care.